Incorporating Cultural Sensitivity Into ESL Curricula To Foster Pragmalinguistic Competence - Paluanova, Khalifa (Indonesian Journal Publisher, 2024)
This study explores strategies for incorporating cultural sensitivity into English as a Second Language (ESL) curricula to enhance learners’ pragmalinguistic competence, the ability to use language pragmatically and appropriately within social contexts. By examining approaches such as culturally relevant content, cross-cultural pragmatics training, and practical language activities, this study analyzes how integrating cultural sensitivity into language instruction fosters learners’ ability to navigate linguistic nuances. Findings suggest that a culturally sensitive curriculum not only enriches linguistic knowledge but also significantly enhances learners’ competence in communicating appropriately across diverse cultural contexts.